Maternal management of newborns treated at the Tulcán Health Center No. 1. Ecuador, 2021-2022 - Clara Elisa Pozo Hernández; Shirley Tatiana Acan Cabrera; Olga Mireya Alonzo Pico; Zuly Rivel Nazate Chuga (Medisur)
Foundation: correct maternal care in the neonatal stage is an elementary factor for the child’s health state. Objective: to describe the maternal management of newborns treated at the Tulcán Health Center No. 1. Methods: observational, descriptive, cross-sectional study on mothers of newborns who attended the Tulcán Health Center N°1 from September 2021 to February 2022. The population studied was 30 mothers. The analyzed variables were: identification of warning signs, elements related to feeding, care and characteristics of the umbilical cord, hygiene in handling the newborn and time of attendance at the first neonatal check-up. A survey was used to collect the information. Results: 90% of the mothers identified the presence of warning signs in their child (33.33% could not feed and/or breathe); 50% of newborns were exclusively breastfed. 26.67% of mothers reported that their baby´s; stomach becomes hard after breastfeeding, and 26.67% reported that their child experienced vomiting after complementary feeding. 46.67% performed the cure with alcohol as care for the umbilical cord and 26.67% presented a red color to it. 33.33% reported washing their hands after changing the diaper and 36.67% cleaned the newborn’s genitals with each diaper change. 16.67% attended the first neonatal check-up consultation on time. Conclusions: there are still inadequacies in the maternal management of the newborn to reduce the risk factors that generate complications.